The International Continence Society (ICS) report on the terminology for male lower urinary tract surgery. Issue 8 (12th October 2020) - Abranches‐Monteiro, Luis; Hamid, Rizwan; D'Ancona, Carlos; Alhasso, Ammar; Dmochowski, Roger; Ecclestone, Hazel; Haylen, Bernard; Mousa, Riyad Al; Onur, Rahmi; Shah, Shahzad; Vasudeva, Pawan; Oelke, Matthias
Abstract: Introduction: In the development of terminology of the lower urinary tract (LUT), due to its increasing complexity, the terminology for male LUT surgery needs to be updated using a male‐specific approach and via a clinically‐based consensus report. Methods: This report combines the input of members of the Standardization Committee of the International Continence Society in a Working Group with recognized experts in the field, assisted by many external referees. Appropriate core clinical categories and a subclassification were developed to give a numeric coding to each definition. An extensive process of 14 rounds of internal and external review was developed to exhaustively examine each definition, with decision‐making by collective opinion (consensus). Results: A Terminology Report for male LUT and pelvic floor surgery, encompassing 149 separate definitions/descriptors, has been developed. It is clinically‐based with the most common diagnoses defined. Clarity and user‐friendliness have been key aims to make it interpretable by practitioners and trainees in male LUT surgery. Figures have not been included to avoid any preference or bias towards a specific procedure. Conclusions: A consensus‐based Terminology Report for male LUT surgery has been produced aimed at being a significant aid to clinical practice and a stimulus for research.